Long Chain Fatty Acids as Modulators of Immune Cells Function: Contribution of FFA1 and FFA4 Receptors - Hidalgo, Maria A. (Front Physiol, 2021)
Long-chain fatty acids are molecules that act as metabolic intermediates and constituents of membranes; however, their novel role as signaling molecules in immune function has also been demonstrated. The presence of free fatty acid (FFA) receptors on immune cells has contributed to the understanding of this new role of long-chain fatty acids (LCFAs) in immune function, showing their role as anti-inflammatory or pro-inflammatory molecules and elucidating their intracellular mechanisms. The FFA1 and FFA4 receptors, also known as GPR40 and GPR120, respectively, have been described in macrophages and neutrophils, two key cells mediating innate immune response. Ligands of the FFA1 and FFA4 receptors induce the release of a myriad of cytokines through well-defined intracellular signaling pathways. In this review, we discuss the cellular responses and intracellular mechanisms activated by LCFAs, such as oleic acid, linoleic acid, palmitic acid, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA), in T-cells, macrophages, and neutrophils, as well as the role of the FFA1 and FFA4 receptors in immune cells.